Surface integrity in metal machining - Part I: Fundamentals of surface characteristics and formation mechanisms - Liao, Zhirong; la Monaca, Andrea; Murray, James; Speidel, Alistair; Ushmaev, Dmitrii; Clare, Adam; Axinte, Dragos; M'Saoubi, Rachid (2020)
The surface integrity of machined metal components is critical to their in-service functionality, longevity and overall performance. Surface defects induced by machining operations vary from the nano to macro scale, which cause microstructural, mechanical and chemical effects. Hence, they require advanced evaluation and post processing techniques. While surface integrity varies significantly across the range of machining processes, this paper explores the state-of-the-art of surface integrity research with an emphasis on their governing mechanisms and emerging evaluation approaches. In this review, removal mechanisms are grouped by their primary energy transfer mechanisms; mechanical, thermal and chemical based. Accordingly, the resultant multi-scale phenomena associated with metal machining are analyzed. The contribution of these material removal mechanisms to the workpiece surfaces/subsurface characteristics is reviewed. Post-processing options for the mitigation of induced surface defects are also discussed.